Efficacy and safety of everolimus for patients with focal cortical dysplasia type 2 - Se Hee Kim; Hoon‐Chul Kang; Yun Ho Roh; Jongsung Hahn; Kyung Lok Min; Seok‐Jin Lee; Donghwa Yang; Han Som Choi; Soyoung Park; Jeong Ho Lee; Sang‐Guk Lee; Se Hoon Kim; et al. (Epilepsia Open)
Abstract Objective This study aimed to evaluate the effectiveness and safety of everolimus in treating seizures associated with focal cortical dysplasia type 2 (FCD 2). Methods A prospective, crossover, placebo‐controlled clinical trial (ClinicalTrials.gov: NCT03198949) enrolled patients aged 4–40 years with pathologically confirmed FCD 2 and a history of ≥3 seizures per month for two out of the 3 months prior to screening. The trial included a 4‐week baseline phase, two 12‐week core phases, and a 29‐week extension phase. Patients received everolimus or placebo in a blinded manner during core phase I, with crossover to the alternate treatment in core phase II. Everolimus dosage started at 4.5 mg/m2/day, targeting a serum level of 5–15 ng/mL. The primary outcome was the proportion of patients achieving ≥50% seizure reduction from baseline in the last month of each core phase. Safety profiles were compared between groups. Results Between May 11, 2017, and June 19, 2020, 21 patients completed the core phases. There was no significant difference in the primary outcome between everolimus and placebo groups (24% vs. 19%, p = 0.66). The patients showed varied responses. Three patients with a pathogenic variant in the MTOR gene or no genetic abnormalities achieved seizure freedom with everolimus in the last month of the core phase, while none of the patients with variants in other genes did. Adverse events, such as mucositis or skin ulceration, were more common with everolimus (19/21 vs. 7/21, p < 0.001). All adverse events resolved without study drug withdrawal. Significance Everolimus treatment for 12 weeks did not show overall superiority in reducing seizures compared to placebo. However, it showed promise, mostly in patients with a pathogenic variant in the MTOR gene, highlighting the need for further research into patient‐specific factors influencing treatment response. The everolimus treatment was generally safe and manageable. Plain Language Summary This study tested everolimus for reducing seizures in patients with focal cortical dysplasia type 2 (FCD 2). While the drug was not more effective than a placebo for most, few patients showed better results, with some becoming seizure‐free. Side effects were common but manageable. More research is needed to understand why certain patients respond better to treatment.